Prototype to mitigate risks for the closure of a company with the support of Information Technologies - Altamirano, Washington A.; Toapanta T. , Moisés; Altamirano, Lenin; Durango, Rodrigo Del Pozo; Orizaga T, Antonio; Maciel A, Roció (Journal of Ecohumanism, 2024)
The problems of business closures (SMEs) are constant in the world and in Ecuador due to the lack of application of appropriate management models that allow the conversion of strategies. The deductive method was used for exploratory research of the information related to the research topic. The objective is to design a prototype to mitigate risks and prevent threats to avoid the closure of this type of companies. The result was a conceptual model to minimize risks, a risk control prototype, a prototype flow chart, a simulation of processes with five scenarios, determination of the formula to detect the probability of closure as an SME and risk analysis and evaluation. It was concluded that the proposed prototype to detect threats and vulnerabilities provides an optimal security model for small and medium-sized companies; as a result of the simulations, a security percentage of 77.92% was established, which means that the greater the number of risks and threats, the greater the probability that a small and medium-sized company will close.